Pathogenic mechanisms contributing to thrombocytopenia in patients with systemic lupus erythematosus. (4th July 2022) - Baroni Pietto, M. Constanza; Lev, Paola R.; Glembotsky, Ana C.; Marín Oyarzún, Cecilia P.; Gomez, Graciela; Collado, Victoria; Pisoni, Cecilia; Gomez, Ramiro A.; Grodzielski, Matías; Gonzalez, Jacqueline; Mariño, Karina V.; Heller, Paula G.; et al.
Summary: Systemic lupus erythematosus (SLE) is an autoimmune condition developing thrombocytopenia in about 10–15% of cases, however, mechanisms leading to low platelet count were not deeply investigated in this illness. Here we studied possible causes of thrombocytopenia, including different mechanisms of platelet clearance and impairment in platelet production. Twenty-five SLE patients with and without thrombocytopenia were included. Platelet apoptosis, assessed by measurement of loss of mitochondrial membrane potential, active caspase 3 and phosphatidylserine exposure, was found to increase in thrombocytopenic patients. Plasma from 67% SLE patients (thrombocytopenic and non-thrombocytopenic) induced loss of sialic acid ( Ricinus communis agglutinin I and/or Peanut agglutinin binding) from normal platelet glycoproteins. Concerning platelet production, SLE plasma increased megakaryopoiesis (evaluated using normal human cord blood CD34+ hematopoietic progenitors), but inhibited thrombopoiesis (proplatelet count). Anti-platelet autoantibody depletion from SLE plasma reverted this inhibition. Overall, abnormalities were more frequently observed in thrombocytopenic than non-thrombocytopenic SLE patients and in those with active disease (SLEDAI≥5). In conclusion, platelet clearance due to apoptosis and desialylation, and impaired platelet production mainly due to inhibition of thrombopoiesis, could be relevant mechanisms leading to thrombocytopenia in SLE. These findings could provide a rational basis for the choice of proper therapies to correct platelet counts in these patients. uf0001